DESENVOLVIMENTO DE NANOPARTÍCULAS DE PLGA E PLGA REVESTIDAS COM POLISSORBATO 80 CONTENDO ÁCIDO GÁLICO - Alves, Aline de Cristo Soares (2015)
Gallic acid (GA), presents several biological activities such as antioxidant and neuroprotective potential, but their physicochemical characteristics limit its use. Considering this, the present study consisted in obtainment, physicochemical and biological characterization of polymeric nanoparticles containing GA with objective to produce formulations can be toward to Central Nervous System. GA was encapsulated into nanoparticles of poly(lactic-co-glycolic acid) (PLGA) and PLGA nanoparticles coated with polysorbate 80 (PS80), by emulsification-solvent method with single emulsion. An analytical method was developed and validated by high performance liquid chromatography in order to allow for reliable GA quantification. The mobile phase of the method consisted of acetonitrile: water: 0.4% acetic acid (50:30:20, v/v/v), in a flow 0.9 mL/min with detection at 271 nm. This method presented a suitable specificity, linearity, interval, precision, detection and quantification limits, accuracy and robustness according to current guidelines. Nanoparticles were characterized in relation to encapsulation efficiency, mean diameter, size distribution, surface potential, identification of functional groups, crystallinity thermal stability, shape and release profile. Nanoparticles without coating and coated demonstrated appropriate physicochemical characteristics with mean size of 223.27 ± 11.80 nm and 228.41 ± 11.16 nm, respectively. After storage for 12 weeks, formulations showed no tendency to flocculation and aggregation, however coated nanoparticles presented zeta potential modified when stored over 8 weeks at room temperature. Thus, is the recommend storage at -20°C temperature. The developed systems present lack of toxicity on red blood cells in concentrations of 40 and 20 üg/mL of GA and antioxidant potential with controlled release and concentration dependent.